Marketing practices in golf and their application for golf club strategy - Chajda, Patrik (2025)
The master’s thesis aims to analyze the marketing environment in golf by examining the use of different marketing tools and strategies, understanding the relationships of various stakeholders as well as exploring the best marketing practices in this sport. The research consisted of semi-structured interviews with 27 respondents, among which were experts, high-ranking members of the Czech Golf Federation, as well as owners and managers of golf clubs and companies. These interviews were further analyzed using a coding method to help broaden the knowledge regarding golf marketing in the Czech Republic. The results showcase the importance of golf clubs’ positioning, proper customer segmentation and understanding the social aspect of golf. The thesis concludes with recommendations for the golf clubs aimed at improving their marketing strategy and their overall understanding of golf marketing.